Aplicación de la prisión preventiva como medida cautelar de última ratio, post sentencia No. 8-20/CN/21 de la Corte Constitucional del Ecuador - Vaca Montalvo, Luis Fabian (2024)
Preventive detention constitutes a legal mechanism whose examination persists due to deficiencies observed in its implementation as a procedural coercive measure. Given its imprecise nature, its application demands a delicate balance between safeguarding public interest and protecting social order against the safeguarding of individuals' fundamental freedoms. The imposition of preventive detention aims to prevent the accused from absconding, especially during trial. For the determination of preventive detention, the Constitutional Court issued Judgment 8-20/CN-21, establishing the principles of exceptionality, necessity, and proportionality, which must be articulated in the reasoning of their application by judges. This research aims to analyze whether judges make reference to the principles mentioned above in imposing preventive detention. Consequently, three specific objectives are derived: firstly, a comparison was made of the requirements for the determination of preventive detention in CAN countries' regulations\; secondly, the arguments of the concurrent vote issued by Justice Ramiro Ávila in the analyzed judgment were analyzed\; finally, through the analysis of cases, the impact of the judgment during the period 2022 and 2023 was measured. In accordance with Resolution 14-2021, it is determined that prosecutors and judges are obliged to provide reasoning as to why alternative precautionary measures to preventive detention are insufficient to ensure the accused's appearance at trial. In conclusion, through a qualitative approach and documentary review, it is found that only 42.85% of the cases examined make reference to the principles enshrined in the studied Judgment.